Synthesis, Characterization and Biological Screening of Azepine Derivative: 2-hydroxy-1,3-di(naphthalene-2-yl)-1H-benzo[b]azepine-5(4H)one - Sharma, Amit; Singh, Ashok Kumar (Journal of Nepal Chemical Society, 2021)
The synthesis of unsaturated heterocyclic compounds containing nitrogen atoms in the ring is very important due to its various biological application in the pharmaceutical industry. Azepine derivatives find numerous application almost every field in medicinal chemistry and some of its are commercially available as drugs. The two-component of azepine derivatives were synthesized by using the aniline and maleic anhydride as a starting material followed by condensation with sodium borohydride in presence of dry benzene, subsequently cyclization by polyphosphoric acid then, finally by an addition reaction with naphthalene-2-ol to form the desired derivative. The formation of the synthesized azepine derivative was confirmed by spectral techniques such as IR, 1H-NMR, and 13C-NMR. The antibacterial assay shows that the synthesized compound (2A) possesses the most highly potent activity in the Bacillus subtilis and moderate activity against other different strains of bacteria and fungi.